Influence of surgical repositioning of mature permanent dog teeth following experimental intrusion: a histologic assessment - Cunha, Robson Frederico [UNESP]; Pavarini, A.; Percinoto, Célio [UNESP]; Lima, JEO (Blackwell Munksgaard, 2002)
The aim of this study was to evaluate, through histologic examination, the effect of surgical repositioning of intruded dog teeth upon the pulpal and surrounding tissues. Thirty teeth in 10 adult dogs, aged 2-3 years, were used. Fifteen teeth were intruded, surgically repositioned and fixed using orthodontics wire, composite resin, and enamel acid conditioning. All these teeth served as the experimental group. The remaining intruded teeth were not treated ( control group). The animals were sacrificed to allow observations at 7,15, and 30 post-operative days. The maxillary and mandibular archs were removed and processed for histologic exam. Based on the methodology and observed results, we concluded that: pulpal necrosis, external root resorption and ankylosis were common sequelae to severe traumatic intrusion; a careful immediate surgical repositioning of severed intruded permanent tooth with complete root formation has many advantages with few disadvantages.
Keywords: dental trauma; tooth luxation; root development; tooth intrusion